Overview of the FTU results. (1st April 2022) - Pucella, G.; Alessi, E.; Almaviva, S.; Angelini, B.; Apicella, M.L.; Apruzzese, G.; Aquilini, M.; Artaserse, G.; Baiocchi, B.; Baruzzo, M.; Belli, F.; Bin, W.; et al.
Abstract: Since the 2018 IAEA FEC Conference, FTU operations have been devoted to several experiments covering a large range of topics, from the investigation of the behaviour of a liquid tin limiter to the runaway electrons mitigation and control and to the stabilization of tearing modes by electron cyclotron heating and by pellet injection. Other experiments have involved the spectroscopy of heavy metal ions, the electron density peaking in helium doped plasmas, the electron cyclotron assisted start-up and the electron temperature measurements in high temperature plasmas. The effectiveness of the laser induced breakdown spectroscopy system has been demonstrated and the new capabilities of the runaway electron imaging spectrometry system for in-flight runaways studies have been explored. Finally, a high resolution saddle coil array for MHD analysis and UV and SXR diamond detectors have been successfully tested on different plasma scenarios.